Can the Internet of Things Persuade Me? An Investigation Into Power Dynamics in Human-Internet of Things Interaction - Kang, Hyunjin; Kim, Ki Joon; Wang, Sai (Frontiers in Psychology, 2022)
The advent of artificial intelligence (AI) and the Internet of Things (IoT) has revolutionized user experience with objects. Things can perform social roles and convey persuasive messages to users, posing an important research question for communication and human-computer interaction researchers: What are the factors and underlying mechanisms that shape persuasive effects of IoT? Bridging the reactance theory and the computers are social actors paradigm, this study focuses on how power dynamics are shaped in human-IoT interactions and its implications on persuasion. Specifically, the study examines the effects of the social role assigned to the IoT mobile app agent and the scope of IoT controlled by the app on users’ perceived power and subsequent persuasive outcomes. The results reveal that when the mobile IoT app is for controlling a smart home, the servant (vs. companion) agent elicits greater perceived power over IoT for users, leading to less threat-to-freedom and better persuasive outcomes, including attitude, intention, and actual behavior. However, such a difference is not observed when the mobile app is for controlling a single smart device (i.e., smart fridge). The study findings offer valuable implications for communication practitioners interested in using IoT as a persuasive tool.